Hotel Portofino. Season one [videorecording (DVD)] - McElhone, Natascha, 1969-; Akhurst, Lucy, 1975-; Binder, Louisa; Carling, Elizabeth, 1967-; Dench, Oliver; Esposito, Pasquale, 1963-; Fasano, Rocco; Frazer, Lily, 1991-; James, Adam; King, Imogen; Morris, Olivia; Pecci, Daniele; et al. (PBS, 2022)
Follows a British family who open a hotel for upper class travelers on the magical Italian Riviera during the Roaring '20s.